Role of Autoantibodies in Acquired Inflammatory Demyelinating Diseases of the Central Nervous System in Children - Rostasy, Kevin; Reindl, Markus (Neuropediatrics, 2013)
The recent detection of aquaporin-4 (AQP4) and myelin oligodendrocyte glycoprotein (MOG) autoantibodies in acquired inflammatory demyelinating diseases, such as neuromyelitis optica, or acute disseminated encephalomyelitis, and multiple sclerosis, in children strongly indicates that B-cell–dependent mechanisms contribute to the pathogenesis. This review aims to give an overview of the role of autoantibodies in inflammatory demyelinating pediatric diseases, with a focus on antibodies to AQP4 and MOG.
Keywords: children; anti-MOG antibodies; MS; ADEM